(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The following article is devoted comparative phonetics, actually similar and different features of double consonants in English and Uzbek languages, the role of comparative method in teaching speaking. It is presented different rules examples for learners, who wants to learn foreign language easy, fast and with fun.